Using the reading matrix to assess effectively the reading comprehension in Sekolah Menengah Kebangsaan Tenghilan, Tamparuli - Sheily Rebecca Motiung (2007)
Reading Comprehension is one of the mysteries in English context, particularly in the Reading area. Unknown to many, including the teachers, students' knowledge on certain Reading Comprehension areas can actually be assessed by using a Reading Matrix. In this time being, a Reading Comprehension test will only be a test with some numerical symbol. Nevertheless, by using a Reading Matrix, teachers can tabulate the student's marks into bands, which consist of Band One to Band Six. Apart from that, from the Reading Matrix itself, the teachers will know the students' strengths and weaknesses by looking at the descriptors provided in the matrix. Each band has different descriptions and it can in a way tell the teachers about the students' performance. Even better, the teacher can also do benchmarking based on the students' marks. This research is about wanting to assess the effectiveness of a Reading Matrix in Reading Comprehension. There are thirty respondents in this study and they were chosen based on their results in the First Semester Examination for English subject. Each form from Form Three to Form Five were represented by ten students who achieved the highest marks in their forms. After they were chosen, they were given a diagnostic test. This test consisted from the real PMR and SPM question papers. Then, after the researcher had the scores, she tabulated the students' marks into bands. Apart from that, based on the bands, the researcher can identify each student's descriptors where it showed the students' strengths and weaknesses. Based on the analysis made, the findings obtained showed that Reading Matrix can indeed help the teachers to tabulate the students' marks, knowing the students' strengths and weaknesses and benchmark the performance of the students. The researcher was able to identify the students' ability of doing Reading Comprehension in terms of Reorganization, Inferential and Literal Comprehension.